Meaningful activities during COVID-19 lockdown and association with mental health in Belgian adults - Cruyt Ellen; De Vriendt Patricia; De Letter Miet; Vlerick Peter; Calders Patrick; De Pauw Robby; Oostra Kristine; Rodriguez-Bailón Maria; Szmalec Arnaud; Merchán-Baeza Jose Antonio; Fernández-Solano Ana Judit; Vidaña-Moya Laura; et al. (BMC, 2021)
Abstract Background The spread of COVID-19 has affected people's daily lives, and the lockdown may have led to a disruption of daily activities and a decrease of people's mental health. Aim To identify correlates of adults' mental health during the COVID-19 lockdown in Belgium and to assess the role of meaningful activities in particular. Methods A cross-sectional web survey for assessing mental health (General Health Questionnaire), resilience (Connor-Davidson Resilience Scale), meaning in activities (Engagement in Meaningful Activities Survey), and demographics was conducted during the first Belgian lockdown between April 24 and May 4, 2020. The lockdown consisted of closing schools, non-essential shops, and recreational settings, employees worked from home or were technically unemployed, and it was forbidden to undertake social activities. Every adult who had access to the internet and lived in Belgium could participate in the survey; respondents were recruited online through social media and e-mails. Hierarchical linear regression was used to identify key correlates. Results Participants (N = 1781) reported low mental health (M = 14.85/36). In total, 42.4% of the variance in mental health could be explained by variables such as gender, having children, living space, marital status, health condition, and resilience (β = −.33). Loss of meaningful activities was strongly related to mental health (β = −.36) and explained 9% incremental variance (R2 change = .092, p < .001) above control variables. Conclusions The extent of performing meaningful activities during the COVID-19 lockdown in Belgium was positively related to adults' mental health. Insights from this study can be taken into account during future lockdown measures in case of pandemics.